2021
DOI: 10.3390/dj9080086
|View full text |Cite
|
Sign up to set email alerts
|

The New Normalcy in Dentistry after the COVID-19 Pandemic: An Italian Cross-Sectional Survey

Abstract: Background: After the first lockdown, Italian dentists resumed their practice while handling several challenges. Reducing contagion risk by complying with the stringent measures recommended by the Italian Ministry of Health for dental activity while also balancing patient needs was a difficult task. This work aims to understand the procedures that were adopted in the second phase of the COVID-19 pandemic (5 May–30 September 2020) and the dentists’ expectations and concerns about returning to normalcy. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
1
8
0
1
Order By: Relevance
“…In the first COVID-19 outbreak period, many countries adopted prudential measures to reduce the risk of contagion, such as suspending elective dental treatments and recommending executing only non-postponable dental treatments. However, after the first waves of COVID-19, the need to restart private and public dental activities has become the first and foremost goal of many dental professionals [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the first COVID-19 outbreak period, many countries adopted prudential measures to reduce the risk of contagion, such as suspending elective dental treatments and recommending executing only non-postponable dental treatments. However, after the first waves of COVID-19, the need to restart private and public dental activities has become the first and foremost goal of many dental professionals [11].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of hydrogen peroxide with chlorhexidine solutions has been shown in vitro to be more effective than either solution alone in preventing transmission of SARS-CoV-2 [ 7 ]. Other studies have shown a decrease in salivary viral load after a 30 s mouth and oropharynx gargle with 15 mL of 1.5% or 3% hydrogen peroxide solution or 0.12% chlorhexidine solution [ 8 ]. Likewise, brief (30 s) rinses with 0.2%, 0.4% or 0.5% povidone–iodine (9 mL) or 0.05% cetylpyridinium chloride (15 mL) have been proven to be effective.…”
Section: Covid-19 and The New Approach To Dental Healthcarementioning
confidence: 99%
“…The World Health Organization (WHO) announced the outbreak of a public health emergency of international concern on 30 January 2020, and a pandemic on 11 March 2020, affecting more than 7 million people in more than 188 countries [ 1 ]. The COVID-19 pandemic has changed the way dentistry has been practiced the world over [ 1 , 2 , 3 , 4 ]. The spread of the virus by aerosols has meant that dental practices the world over have had to find ways to contain aerosols in practices [ 5 ].…”
Section: Introductionmentioning
confidence: 99%